2010
DOI: 10.1186/1475-2875-9-231
|View full text |Cite
|
Sign up to set email alerts
|

Malaria risk in Corsica, former hot spot of malaria in France

Abstract: BackgroundThe prevalence of Plasmodium falciparum and Plasmodium vivax malaria was very high in Corsica just before the Second World War. The last outbreak was in 1972 and the most recent indigenous case was in 2006.ResultsAnalysis of historical data shows that anopheline vectors were abundant. Recent surveys demonstrated that potential vectors are still present in Corsica, despite the likely disappearance of Anopheles sacharovi. Moreover, P. falciparum can develop experimentally into these mosquitoes, notably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 17 publications
1
37
0
Order By: Relevance
“…Recent studies of An. labranchiae populations collected in France and Italy confirmed that this species is receptive to P. falciparum, but exhibits a low vector competence [23,24]. …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of An. labranchiae populations collected in France and Italy confirmed that this species is receptive to P. falciparum, but exhibits a low vector competence [23,24]. …”
Section: Introductionmentioning
confidence: 99%
“…labranchiae. 49,50 Moreover, An. labranchiae has also been involved in autochthonous transmission of P. vivax in Corsica, Greece, and Italy.…”
Section: Discussionmentioning
confidence: 99%
“…In Corsica, where An. labranchiae still present in high densities in different regions (Toty et al, 2010), autochthonous P. vivax malaria transmission has been diagnosed, probably via the bite of a local Anopheles mosquito infected with P. vivax from a patient who had acquired infection in Madagascar (Armengaud et al, 2006). The second most important malaria vector of Corsica, Anopheles sacharovi, has not been detected in the island since 2002 (Toty et al, 2010).…”
Section: Malaria Receptivity In Southern Europementioning
confidence: 99%
“…Nevertheless recent researches with populations from Corsica have indicated that P. falciparum cycle can be successfully completed in An. labranchiae (Toty et al, 2010). Furthermore An.…”
Section: Infectivitymentioning
confidence: 99%